THE EFFECTIVENESS OF COLLABORATIVE STRATEGIC READING (CSR) IN TEACHING CRITICAL READING TO EFL STUDENTS - Nanik Sri Rahayu (Jurnal Bahasa Lingua Scientia, 2019)
Critical reading is a hot issue nowadays. Students in all levels, especially in tertiary education are pursuing the need of critical reading especially in English reading test. However, it is not an easy job for the students when they are asked to complete the reading task focusing on critical reading. Many students get confused, trapped in the distractor or even get frustrated when they cannot answer the questions. Collaborative strategic reading is one of the strategy in teaching reading which is hypothesized to be able to help the students in answering questions in critical reading tests. This research used quasi-experimental design with quantitative approach. To collect the data, the researcher used research instrument in form of test.  The result of the study revealed that the significant value is 0.000 which was smaller than the significant level (0.050). It could be concluded that using collaborative strategic reading (CSR) strategy was effective to increase the students’ critical reading achievement at English education department at IAIN Tulungagung. It is suggested that collaborative strategic reading  (CSR) strategy can be used as alternative strategy for English teachers in teaching and learning critical reading text.